2011
DOI: 10.1007/s00520-011-1129-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impairment in patients urgently referred for prostate and bladder cancer investigations: the role of trait emotional intelligence and perceived social support

Abstract: Patients urgently referred for urological cancer investigations are a group at risk of psychological impairment and may benefit from healthcare professional support. High trait EI was associated with less state anxiety, less worry and higher perceived social support. There were few consistent effects of perceived social support on psychological impairment. Consideration should be given to the inclusion of trait EI in future models of trauma adaptation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 27 publications
3
27
0
1
Order By: Relevance
“…Individuals with a higher TEI show greater self-efficacy in coping with stress, making it probable that their QoL is more favorable compared with people with lower TEI scores who show a lower self-efficacy (34Y36). A study on patients with urologic cancer concludes that patients with a lower TEI score are more at risk of psychological impairment and that TEI is a major predictor of psychological adaptation for which patients can be helped professionally, both psychologically and socially (40). These results are in line with a meta-analysis on the relationship between TEI and health performed by Martins et al, which has shown that TEI could be a predictor of health (41).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Individuals with a higher TEI show greater self-efficacy in coping with stress, making it probable that their QoL is more favorable compared with people with lower TEI scores who show a lower self-efficacy (34Y36). A study on patients with urologic cancer concludes that patients with a lower TEI score are more at risk of psychological impairment and that TEI is a major predictor of psychological adaptation for which patients can be helped professionally, both psychologically and socially (40). These results are in line with a meta-analysis on the relationship between TEI and health performed by Martins et al, which has shown that TEI could be a predictor of health (41).…”
supporting
confidence: 87%
“…They can help patients find a way to improve management of their emotions. Social support and psychological support seem to be helpful to improve the emotional impairment in patients with, for example, cancer (40). A future goal of the current research group is to start a cognitive behavior therapy program focused on the psychosocial consequences of the medical condition and evaluate its effects.…”
Section: Discussionmentioning
confidence: 97%
“…Multiple studies have demonstrated that this construct is involved in many important life domains, including medicine (e.g., Costa et al 2014b;Smith et al 2012), stress (e.g., Laborde et al 2011), mental health (Martins et al 2010;Petrides et al 2011), neuropsychology (Mikolajczak and Luminet 2007), leadership and entrepreneurialism (Ahmetoglu et al 2011;Zampetakis et al 2009). A growing number of studies have revealed mediating, moderating, and incremental trait EI effects over various relevant variables including general health, socio-emotional outcomes, and life satisfaction (e.g., Johnson et al 2009;Mavroveli et al 2009;Petrides et al 2007a, b;Saklofske et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The present study focuses on trait EI, defined as a constellation of selfperceptions located at the lower levels of personality hierarchies. High trait EI predicted less state anxiety and worry in cancer patients (Smith, Turner, et al, 2012). High trait EI predicted less state anxiety and worry in cancer patients (Smith, Turner, et al, 2012).…”
Section: What Does This Study Add?mentioning
confidence: 92%